Optimalisasi Pengaman Hewan dalam Upaya Mengurangi Gangguan pada Penyulang SI-03 di ULP Singkil Untuk Meningkatkan Kinerja SAIDI dan ENS - Rosadi, Muhammad Yudhistifani; Hamdani, Hamdani; Tarigan, Adisastra Pengalaman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Electric reliability of the electrical distribution network is an essential element in ensuring the smooth supply of energy to customers. At ULP Singkil, feeder SI-03 plays a vital role in meeting the electricity needs of the local community and industries. However, this network faces significant challenges in maintaining the stability of the electricity supply, particularly due to external disturbances caused by animals such as birds, monkeys, and reptiles. These disturbances can damage network components such as insulators and conductors, leading to short circuits, equipment damage, and power outages that affect customers. This problem is further exacerbated by the geographical conditions of ULP Singkil, which is dominated by rural and forested areas, increasing the intensity of interaction between animals and the electricity network. This study aims to evaluate and propose steps for optimizing daily maintenance on feeder SI-03, especially in handling animal-related disturbances. Based on disturbance data from January to March 2024, the SAIDI and ENS values at ULP Singkil show results that exceed the targets, indicating the need for improvements. As an innovative solution, this research proposes the use of used tires mounted on electrical pole brackets to reduce disturbances caused by animals.